Intelligent Campus and English Visual Education System Design Based on Internet of Things - Qi Li (Advances in Multimedia)
With the continuous development of the Internet of Things technology, learning and acquiring knowledge through Internet will become an important way for human beings to learn, work, and conduct research. In the field of English language teaching, the cutting-edge research on the Internet of Things-based interactive teaching models is important. The intelligent campus is a new type of campus built aided by advanced techniques such as machine learning and the Internet of Things. In the smart campus, the classroom usually consists of a tangible physical space and an invisible digital space, which can be used to support teaching content through various types of intelligent equipment, promote classroom interaction, and achieve more convenient visualization of educational functions. Based on the initial results of the Internet of Things research, this research establishes a visual education system based on the Internet of Things. At the same time, the Internet of Things is used to study the interactive English teaching mode in order to improve the level of English teaching and thus enhance the technology level of the intelligent campus.